Materias primas alternativas para pequeños productores de cerdos como complemento nutricional. - Castro Piza, Angie Yazmín (2022)
In the present study, bibliographical research was carried out on "Alternative raw materials for small pig producers as a nutritional complement", whose main objective is to identify and describe new alternatives that contribute to the economy of the small producer. In a market that increases its demand for products derived from pork, it is necessary to publicize various raw materials that in some way allow to reduce feed costs. In production costs, feed represents between 70 to 80% of production costs, so maintaining high pig production accompanied by good profitability requires the use of traditional inputs based on corn and soy; which has made the increase in prices one more challenge for producers, who have seen the small pig industry threatened, one more reason to implement new elements in the diet. Among the alternatives that can be implemented we have: cassava, banana, whey, sweet potato, palm kernel, alcohol distillation residues, among others; These elements are considered easy to obtain, since we often find them as waste from other industrialization processes and taking advantage of them would be an opportunity to optimize resources. At the end of this study, it is concluded that producers should include alternative food sources as a nutritional supplement, thus allowing the use of agricultural by-products, which are often easily found in the areas where pigs are produced; Therefore, increasing the economic income of producers requires that nutritional alternatives be sought that replace balanced foods.